Economic fundamentals of health care in the Kyrgyz Republic - Choyubekova, G.A.; Kocherbayeva А.А. (BUKETOV BUSINESS REVIEW, 2019)
In the article the economic aspects of the activities of economic entities of health care system of the Kyrgyz Republic are examined. The issues of financing the health care sector were considered, the sources of financing and subsidizing the provision of medical care at various levels of management were studied. The current problems that constrain the development of the health care system in the Kyrgyz Republic are indentified, including those associated with the formation of effective sources of financing the medical industry, are identified. The structure of the health care system is analyzed, and the system for obtaining grants for the modernization of the health care infrastructure is revealed. The current macroeconomic conditions are considered, and the current situation has led to the fact that the coverage of health insurance in the country remains low; factors that have an impact on the economy as a whole and on the formation of the state budget in particular are indentified, there is a shadow economy; factors leading to the formation of a financial gap as unreasonable hospitalization, which indicate the inefficient use of available resources. The problems in the field of health care financing were identified and ways to solve them through appropriate measures were proposed. Priority directions were considered with a view to strengthening the economic basis of the national health care system and forming the financial basis for the life support sector of the Kyrgyz Republic.